Audit procedures applied for auditing General and Administrative Expense in manufacturing company at Nexia STT - Hoang, Tuan Anh (H. : ĐHQGHN, 2020)
This paper is aiming to better understand the process of auditing General and Administrative expense in manufacturing company at Nexia STT. This research paper discovers the process of auditing General and Administrative expense in details, and furthermore understand the strengths and limitations. To achieve that the researcher had obtain some techniques in the research paper, the first thing is observational and descriptive to know more about the progression of audit General and Administrative expense. Moreover, to procure deeper knowledge about the potential errors and frauds that may happened throughout the year, to make sure that the mistakes never occur again. To make the points stronger and more well-defined, research methods were added, like using the data source to have more details of all accounts related to General and Administrative expense. This research paper shown that there were total of six steps from making the lead schedule to the TỐ work, all the steps were details and aligned with the laws and the regulations in order to complete the process of auditing General and Administrative expense at manufacturing companies. After gone through the process there were some strengths and limitations, on the one side, the strengths were the whole audit process from Nexia was strictly aligned with the Vietnamese Accounting standard, want to find out errors and frauds. On the other side, there were limitations that should consider, in the busy season the company still use interns to do some of the procedures, or some other transactions related to the work of another auditors, hence that they might not checked themselves. All in all, it is hoped that this research paper can benefit for further studying of General and Administrative expense.